Genome-Wide Screening of Aberrant Methylation Loci for Nonsyndromic Cleft Lip - Xiao-Yan Xu; Xiao-Wei Wei; Wei Ma; Hui Gu; Dan Liu; Zheng-Wei Yuan (Chinese Medical Journal, 2018)
Background: The pathogenicity of cleft lip (CL) is pretty complicated since it is influenced by the interaction of environment and genetic factors. The purpose of this study was to conduct a genome-wide screening of aberrant methylation loci in partial lesion tissues of patients with nonsyndromic CL (NSCL) and preliminarily validate candidate dysmethylated genes associated with NSCL. Methods: Fifteen healthy and sixteen NSCL fetal lip tissue samples were collected. The Infinium HumanMethylation450 BeadChip was used to screen aberrant methylation loci in three NSCL and three healthy lip tissues. The differential methylation sites and functions of the annotated genes between NSCL and healthy lip tissues were analyzed using minfi package of R software, cluster analysis, Gene Ontology (GO) annotation, and metabolic pathway annotation. Gene expression was assessed in nine differentially methylated genes by real-time polymerase chain reaction (PCR). The transcriptions mRNA levels of three out of nine candidate genes were downregulated remarkably in NSCL lip tissues, and these three genes' abnormal methylation loci were validated by pyrosequencing in 16 NSCL cases and 15 healthy cases. Results: In total, 4879 sites in the genes of NSCL odinopoeia fetuses showed aberrant methylation when compared with normal lip tissue genome. Among these, 3661 sites were hypermethylated and 1218 sites were hypomethylated as compared to methylation levels in healthy specimens. These aberrant methylation sites involved 2849 genes and were widely distributed among the chromosomes. Most differentially methylated sites were located in cytosine-phosphoric acid-guanine islands. Based on GO analysis, aberrantly methylated genes were involved in 11 cellular components, 13 molecular functions, and a variety of biological processes. Notably, the transcription of DAB1, REELIN, and FYN was significantly downregulated in lesion tissues of NSCL fetus (P < 0.05). Pyrosequencing results validated that there were two loci in DAB1 with high methylation status in patient tissues (P < 0.05). Conclusions: We detected numerous aberrantly methylated loci in lesion tissues of NSCL fetus. Aberrant gene expression in the REELIN signaling pathway might be related with NSCL. Decreased transcription of DAB1, a member of REELIN signal pathway, resulted from its abnormal high methylation, which might be one of the factors underlying the occurrence of NSCL.